2020
DOI: 10.21203/rs.3.rs-73016/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diselenide Crosslinks for Enhanced and Simplified Oxidative Protein Folding

Abstract: The oxidative folding of proteins has been studied for over sixty years, providing critical insight into protein folding mechanisms. Hirudin, the most potent natural inhibitor of thrombin, is a 65-residue protein with three disulfide bonds, and is viewed as a folding model for a wide range of disulfide-rich proteins. Hirudin’s folding pathway is notorious for its highly heterogeneous intermediates and scrambled isomers, which plague its folding rate and yield in vitro. Aiming to overcome these limitations, we… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…We also checked the folding of hirudin as an alternative candidate, where it folds to the native state through heterogenous pathway that involve the formation of non‐native intermediates [42] . However, under anaerobic conditions and in the presence of catalytic amounts of SELENOF Trx , hirudin folded through the established pathway [39,42] showing no difference when compared to the control experiment (Figure S12c and d).…”
Section: Figurementioning
confidence: 93%
See 1 more Smart Citation
“…We also checked the folding of hirudin as an alternative candidate, where it folds to the native state through heterogenous pathway that involve the formation of non‐native intermediates [42] . However, under anaerobic conditions and in the presence of catalytic amounts of SELENOF Trx , hirudin folded through the established pathway [39,42] showing no difference when compared to the control experiment (Figure S12c and d).…”
Section: Figurementioning
confidence: 93%
“…Weissman and Kim studied BPTI folding in the presence of PDI, [37] which increased dramatically both the yield and the rate of the native state formation. In BPTI folding, PDI functions as a catalyst for the rate‐determining intramolecular rearrangement from the trapped intermediates N’ and N* to form NnormalSnormalHnormalSnormalH , the direct precursor to N. Furthermore, previously the Sec‐substituted BPTI [38] and hirudin [39] analogs, as well as other proteins [40] have been investigated, and in all cases, Sec was found to enhance the folding kinetics and yields of these proteins. We have initiated our studies on BPTI by following previously reported folding conditions [40] .…”
Section: Figurementioning
confidence: 99%
“…[ 17 ] This method avoids the need for strong oxidizing conditions, enabling broader compatibility with common synthetic peptide functionalities, and has been widely adopted in a broad range of applications. [ 20–37 ]…”
Section: Introductionmentioning
confidence: 99%
“…17 This method avoids the need for strong oxidizing conditions, enabling broader compatibility with common synthetic peptide functionalities, and has been widely adopted in a broad range of applications. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] The increased use of C-terminal α-hydrazides in peptide chemistry creates a demand for robust synthetic tools for accessing these moieties. A number of methods have been published to allow access to C-terminal hydrazides on both synthetic 15,16,38 and expressed 15,39,40 peptides and proteins.…”
Section: Introductionmentioning
confidence: 99%